Pidie Jaya City and Rupture Area after the Earthquake That Happened In December 7, 2016 - Deassy Siska; Adi Safyan; Nova Purnama Lisa; Maryana Maryana; Sisca Olivia; Lydia Rosnita; Andrean Vesalius; Eridawati Eridawati; Asrillah Asrillah (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2018)
Pidie Jaya has experienced a very severe earthquake on December 7, 2018. The depth of the epicenter is estimated to be approximately 8.7 km. Data processing was conducted by using Matlab and Geopsy software and mapping of Rupture and Pidie Jaya area through GIS software. It is obtained from the results of research through data signals of Pidie Jaya earthquake that the direction of earthquake rupture moving from the northern center of the epicenter to the east with a range of back azimuth value of 30.1o - 46.5o with the duration of rupture is 100 seconds. For 100 seconds the direction of the rupture undergoes a twist in the 20th seconds that is initially heading northeast in the direction of 40o from the epicenter. Rupture area is an area prone to earthquake disasters. This research can be a basic reference for the development of the pidie city spatial pattern.